About the regularization of a linear nondegenerate difference-algebraic boundary-value problem by the perturbation of the boundary condition (Neliniini Kolyvannya, 2025)
Conditions for regularization of a linear nondegenerate difference-algebraic boundary-value problem by the perturbation of the boundary condition are found.